Multicenter study of factors associated with nonsurvival in hospitalized periparturient goats - Daniela Luethy; Catalina Cabrera; Lisette M. Coll‐Roman; Ashley R. VanderBroek; Anje G. Bauck; Jenna W. Stockler; Clare Scully; Audrey A. Kelleman; Evelyn E. Mackay; Sarah M. Depenbrock; Marie‐Eve Fecteau; Michelle Abraham; et al. (Journal of Veterinary Internal Medicine)
Abstract Background Periparturient reproductive complications appear to be common in hospitalized goats. More information is needed about periparturient reproductive complications and survival in goats with these conditions. Objective Identify exposure factors associated with nonsurvival in periparturient does hospitalized ≤1 day or ≥2 days. Animals A total of 198 periparturient does presented to 9 university veterinary hospitals from October 2021 to June 2022. Methods Multicenter, matched case‐control study. Conditional logistic regression was used to identify exposure factors associated with nonsurvival in periparturient does hospitalized ≤1 day or ≥2 days. Results Overall doe survival was 79% (156/198). Survival in the 1st day of hospitalization was 71% (52/73) and survival in does hospitalized ≥2 days was 83% (104/125). Among goats hospitalized ≤1 day, labor duration before admission (odds ratio [OR] = 4.8; P = .04), uterine tears (OR = 48.2; P < .001), and vaginal/perineal trauma diagnosed during hospitalization (OR = 6.2; P = .03) were associated with nonsurvival. Among goats hospitalized ≥2 days, factors associated with nonsurvival included labor duration before admission (OR = 6.2; P = .004), pregnancy toxemia (OR = 6.07; P = .04), and Cesarean section (OR = 11.35; P = .02). Conclusions and Clinical Importance Longer labor duration before admission is an important predictor of nonsurvival in hospitalized does. Clients should be educated that early detection and veterinary care are critical for improving outcome in periparturient does.